The media in the structure of social processes - Buzovsky, Ihor I. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the role and place of mass media in the structure of social processes. The features of information influence on the personality in modern conditions of development of society are analyzed, the model of formation of «norm Vector» is developed, the role of mass media in formation of behavioral attitudes of the personality is revealed. The content of the negative and positive information impact on the behavioral attitudes of the individual is revealed.